ONLINE COLLABORATIVE WRITING TO ENHANCE STUDENTS’ WRITING MOTIVATION AND WRITING ABILITY - Amanda Az zahra; Desty Febria (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2023)
Writing has always been a vital skill in English language learning. However, many students struggle with writing. Students are unable to think of what to write despite the teacher providing a topic, spend too much time thinking and use the same vocabulary repeatedly. Furthermore, students were considered to have low motivation for writing and often copied existing paragraphs. The thought of writing is difficult for them, as well as laziness to develop their own ideas. To overcome the writing problem and provide an enjoyable classroom, the author applied an online collaborative writing method through Canva Application to enhance students’ motivation, writing ability, and help the teaching and learning process. This research used the cycle of Classroom Action Research; planning, acting, observing, and reflecting. By giving them pre-test and post-test, mean scores were compared to determine any improvement with writing skills, then a close-ended questionnaire was distributed to investigate their perception to the strategy implemented. This research implied that the strategy was effective to enhance students' writing ability and motivation. The results of students’ tests were improved by 1.31 along with result of the questionnaire about their perception towards online collaborative that almost students agreed that online collaborative writing was a method to enhance their writing motivation. Students writing ability was increased in content, organization, language use, vocabulary, and mechanic aspect.